Prospective longitudinal course of aggression among adults with bipolar disorder. (23rd December 2013) - Ballester, Javier; Goldstein, Benjamin; Goldstein, Tina R; Yu, Haifeng; Axelson, David; Monk, Kelly; Hickey, Mary Beth; Diler, Rasim S; Sakolsky, Dara J; Sparks, Garrett; Iyengar, Satish; Kupfer, David J; et al.
<x xml:space="preserve">Abstract</x> Objectives Bipolar disorder (BP) has been associated with increased aggressive behaviors. However, all existing studies are cross‐sectional and include forensic or inpatient populations and many do not take into account the effects of comorbid conditions. The goal of this study was to evaluate the longitudinal course of aggression among adult outpatients with BP compared with non‐BP patients and healthy controls. Methods Subjects with bipolar I disorder (BP‐I)/bipolar II disorder (BP‐II) (n = 255), those with non‐BP psychopathology (n = 85), and healthy controls (n = 84) (average 38.9 years, 78.7% female, and 84.9% Caucasian) were evaluated at intake and after two and four years of follow‐up. Aggression was self‐rated using the Aggression Questionnaire (AQ). Comparisons were adjusted for any significant demographic and clinical differences and for multiple comparisons. For subjects with BP, associations of AQ with subtype of BP, current versus past mood episodes, polarity and severity of the current episode, psychosis, and current pharmacological treatment were evaluated. Results In comparison with subjects with non‐BP psychiatric disorders and healthy controls, subjects with BP showed persistently higher total and subscale AQ scores (raw and T‐scores) during the four‐year follow‐up. There were no effects of BP subtype, severity or polarity of the current episode, psychosis, and current pharmacological treatments. Subjects in an acute mood episode showed significantly higher AQ scores than euthymic subjects. Conclusions BP, particularly during acute episodes, is associated with increased self‐reported verbal and physical aggression, anger, and hostility. These results provide further evidence of the need for treatments to prevent mood recurrences and prompt treatment of acute mood episodes in subjects with BP.